A unified bus voltage regulation and MPPT control for multiple PV sources based on modified MPC in the DC microgrid - Yang, Pengcheng; Peng, Yonggang; Xia, Yanghong; Wei, Wei; Yu, Miao; Feng, Qifan (Frontiers in Energy Research, 2022)
This paper proposes a unified voltage regulation and maximum power point tracking (MPPT) method for photovoltaic (PV) sources in islanded direct current (dc) microgrids based on modified model predictive control (MPC). The method enables the PV sources to track the maximum power, as well as serve as voltage sources for dc-bus voltage regulation, when their available power is sufficient. Based on the proposed modified predictive model, the desired duty cycles can be calculated and directly applied on the PV sources in a constant switching frequency without a modulator. Real-time laboratory tests show that the PV sources can support the dc-bus voltage without energy storage (ES), and proportionally share the load. Moreover, power oscillations and voltage ripples of the modified MPC get greatly attenuated compared with the traditional MPC under the same sampling frequency.